The Effect of Human Resource Development, Work Discipline and Work Climate on Employee Performance in Motui District, North Konawe Regency - Neliwati, Neliwati; Abbas, Bakhtiar; Sabilalo, Mahmuddin A. (International Journal of Management and Education in Human Development, 2024)
This study aims to find out and analyze (1) The influence of human resource development on employee performance in Motui District, North Konawe Regency; (2) The effect of work discipline on employee performance in Motui District, North Konawe Regency; and (3) The effect of work climate on employee performance in Motui District, North Konawe Regency. The determination of the number of samples in this study is by using the census method, namely the number of samples taken from the entire population of 49 employees. The data analysis technique in this study uses Partial Least Square (PLS). Based on the results of the study, it can be concluded that (1) Human resource development has a positive and significant effect on employee performance in Motui District, North Konawe Regency; (2) Work discipline has a positive and significant effect on employee performance in Motui District, North Konawe Regency; and (3) Work climate has a positive and significant effect on employee performance in Motui District, North Konawe Regency.